Crushing performance and optimization of bio-inspired multi-cell columns - Ozturk, Ismail (Walter De Gruyter Gmbh, 2023)
Multi-cell columns inspired by diatom algae have been examined regarding crashworthiness. Crushing simulations have been conducted for AA2024-T351, B1500HS-O25, and a combination of these materials. The highest specific energy absorption and lowest peak crushing force value were obtained with a homogenous AA2024-T351 column. Single and multi-objective optimization studies have been conducted with this column to find the best design. This design could be used in crash-box-like structures in automotive design.
Keywords: bio-inspired; multi-cell column; optimization; peak crushing force (PCF); specific energy absorption (SEA)